Laser-Sintered versus Conventional Cobalt-Chromium Bars in Implant-Supported Complete Mandibular Overdentures: An In Vitro Strain Analysis Comparative Study - Sidky, Mohamed M.; Elsayed, Mohamed Ezzat; Zaky, Sara (European Journal of General Dentistry, 2025)
The aim of this study was to compare the effect of laser-sintered and conventional cobalt-chromium bars on strain distribution around implants in mandibular implant-supported overdentures.A three-dimensional (3D) epoxy resin model for completely edentulous mandible was used for this study. Two implants were placed in the canine region, and the 3D model was scanned by a laboratory scanner. Twelve cobalt-chromium bars were divided into two groups. Group 1 includes six bars that were designed by software and created using the laser sintering method. Group 2 includes six bars that were made using computer-aided design and computer-aided manufacturing to make a wax model, fabricated by a conventional lost wax-casting technique. Each implant was surrounded by four channels in the epoxy resin model, and four strain gauges were cemented. A universal testing machine was used to apply the load, and a strain measuring analysis was performed.Null hypothesis was rejected as there was significant difference in strain distribution around implants between both groups for the microstrains around the implants in bar-retained implant-supported prostheses, in both bilateral and unilateral results.The laser sintering method showed better results in comparison with conventional methods in fabrication of bar-retained implant-supported prostheses due to less trauma to the implant and supporting structures.
Keywords: cobalt-chromium bars; implant supported overdenture; direct 3D printing; strain gauge analysis